2020
DOI: 10.1136/bmjinnov-2019-000369
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards digital health tools for outpatient cirrhosis management in patients with decompensated cirrhosis

Abstract: BackgroundTechnology represents a promising tool to improve healthcare delivery for patients with cirrhosis. We sought to assess utilisation of technology and preferred features of a digital health management tool, in patients with an early readmission for decompensated cirrhosis.MethodsWe conducted a cross-sectional study of patients readmitted within 90 days for decompensated cirrhosis. A semistructured interview obtained quantitative and qualitative data through open-ended questions.ResultsOf the 50 partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
(28 reference statements)
1
10
0
Order By: Relevance
“…In an interview study of 50 patients admitted for a complication of cirrhosis, 79% were interested in using a digital health management tool that could provide information about cirrhosis and 75% were interested in more education on a low‐salt diet. ( 18 )…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an interview study of 50 patients admitted for a complication of cirrhosis, 79% were interested in using a digital health management tool that could provide information about cirrhosis and 75% were interested in more education on a low‐salt diet. ( 18 )…”
Section: Resultsmentioning
confidence: 99%
“…In an interview study of 50 patients admitted for a complication of cirrhosis, 79% were interested in using a digital health management tool that could provide information about cirrhosis and 75% were interested in more education on a low-salt diet. (18) Few cirrhosis education programs were described in our literature review (Table 2), and the ones that exist demonstrated improvement on a small scale. Volk et al (13) administered a knowledge assessment questionnaire to 115 patients before and after an educational intervention (concise educational booklet), with scores increasing from 53% to 67% before and after intervention, respectively.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Nevertheless, the intervention includes valuable educational material and offers the potential to continue communication with the treating teams after discharge for most of the clinical issues that underlie readmission, such as hepatic encephalopathy, gastrointestinal bleeding, ascites, and medication management [3,9]. This approach was tested by Bloom et al [11] in a cross-sectional survey where theoretical acceptance of an app that would require similar communications as currently being tested with Patient Buddy was considered to be acceptable to most patients. This finding is in contrast to the results of this study, likely because unlike the theoretical constructs in the prior study, the dyads had to agree to be randomized for a 30-day trial in real life in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Technology represents a promising tool to facilitate the management of ascites by increasing the quality and quantity of patient-provider communication about weight data. In a recent interview study of patients with an early readmission for decompensated cirrhosis, the majority stated that they would use a smartphone to manage their condition, particularly if it was able to transmit weight data to their provider [ 13 ]. Retrospective and survey studies suggest that programs with enhanced outpatient care can improve outcomes for patients with ascites [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%